International experience of administrative legal regulation of insurance in innovative and investment activity - Шапенко, Людмила Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Ukraine that chose a direction of innovative development requires activation of innovation and investment activity among all subjects of commercial activity. This process is accompanied by many investment and financial risks, most of which may be minimized by methods of insurance. The analysis of insurance shows the rapid growth of the insurance market in the period of independence, but today there are some difficulties that are caused by decrease of activity of the national financial market. One of the problems of this situation is insufficient government regulation, including administrative and legal, as well as inconsistency of actions in relation of organization of state supervision in the sphere of insurance. Due to globalization and integration processes nowadays it is important to appeal to the international experience of administrative and legal regulation of insurance in developed countries, where there is sustainable economic development for many years. Indeed, administrative and legal regulation of insurance, including the sphere of innovation and investment activity, is the integral part of the relations of the government and insurance companies. Optimal combination of regulation and deregulation of insurance is important because the result of this is reduction of pressure on insurance companies from the side of the state, balance of interests of subjects of insurance relations and the bodies of state power that regulat them. Consideration of different approaches to administrative and legal regulation of insurance in the leading countries of the world suggests that the most widespread model is megaregulator of the financial market, which oversees the insurance market, bank institutions and securities market. Conceptual approaches to create the single consolidated regulator are defined in Ukraine, but before such a system of regulation of the national financial market is provided it is needed to consider the experience of the United Kingdom, where the system of megaregulator did not justify itself.